Relationship between Interest Rate and Rate of Inflation in India - Rathore, D; Deora, KPS; Chhabra, I; Deora, RPS (International Journal of Computer Sciences and Engineering, 2025)
This study examines and analyzes the probable, empirically existing relationship between interest rate and rate of inflation in Indian economy, The Interest rate and the inflation rate has always been the most debating subject in the Indian economy. All central banks implement some kind of monetary policy to achieve their economic goals. And India is no exception. Interest rates receive a lot of attention in the media and play an important role, in formulation of government policy. Changes in the rate of interest can have significant impact on the way individuals or other entities behave as investors and savers. These changes in investment and saving behavior subsequently have an impact on the economic activities of a country. The motivation for the study comes from two perspectives. Firstly, India is an emerging economy and findings of the study would help policy makers to take suitable policy initiatives in that economy. Secondly, all empirical studies concerning the Fisher hypothesis have primarily focused on USA and European economies. The conclusion differs from country to country. Also the important methodological issue is whether Wholesale Price Index (WPI) or the Consumer Price Index (CPI) is to be taken for inflation. Then the Treasury bill yield rate is often taken as the nominal interest rate. To achieve the objective of the study Augmented Dickey Fuller unit root test was performed, to check for Stationary. The Akaike criterion, Hannan-Quinn and Durbin-Watson test were also conducted for finding relationship in the Indian context.